Conceptual Metaphors and Pragmatics Meanings in Christina Perri’s Songs: “Hurt”, “Blue” & “Mothers” - Herlyna Herlyna; Retno Ramadhina; Aura Pradita (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
the writer raises the issue of types of conceptual metaphors and the pragmatic meaning of these metaphorical expressions found in Christina Perri's songs entitled "Hurt", "Blue" and "Mothers". The aim is to introduce the types of conceptual metaphors and the pragmatic meanings contained in them to make it clear that collaboration between concept metaphors and pragmatics can be done and is becoming increasingly familiar to most people, especially in the field of linguistics. This research applies George-Lakoff's (2013) conceptual metaphor theory and Brown-Yule's (2013) pragmatics theory to find the meanings contained therein. A qualitative descriptive approach will be used in this research. The results of the research confirm that there are 3 types of conceptual metaphors in the three selected songs and in conveying their meaning, Christina Perri conveys the meaning contained in the conceptual metaphor expressions conveyed contextually not based on the background of the song lyrics created.